EXAMINATION OF TEACHERS' DIGITAL QUALIFICATIONS. - Sarıdemir, Cihan; Ertem, Hasan Yücel (Route Educational & Social Science Journal (Ress Journal), 2025)
This study aims to examine the digital competencies of teachers in today's educational environment. With the rapid advancement of technology, digital tools and resources play an important role in the educational process, leading to the digital competence of teachers becoming more and more important. The main purpose of the study is to investigate teachers' digital competencies, to understand their skills in using digital technologies effectively and the impact of this use on students' learning experiences. In this study, the importance and necessity of teachers' digital competencies emerge with the idea that students can learn more effectively in an integrated learning environment with technology. It focuses on the skills of teachers at various levels to use digital technologies, their ability to create teaching materials, and their ability to use online learning platforms effectively. The descriptive survey model was used in the quantitative study. The study group consists of 214 teachers working in the pre-school, primary, secondary and high school levels of the Ministry of National Education in the province of Zonguldak in the 2022-2023 academic year. The "Personal Information Form", which includes information such as age, gender, professional experience, graduation type and school type, was filled in completely by all participants. Considering the principle of voluntariness among the teachers, the sample selection was created with the purposeful sampling method, which is one of the non-random sampling methods. "Digital Teacher Competence Scale" was used as data collection tool. Arithmetic mean, standard deviation, Independent t- Test, and one-way analysis of variance (ANOVA) were used to analyze the data using the SPSS (Statistical Package for Social Sciences) program. As a result of the analyzes made, it is seen that the teachers are perceived as "partially suitable/partially not suitable for me". This study highlights the importance of teachers' digital competencies in the education system. The results of this study aim to form a basis for the development of policy recommendations and related training programs to increase teachers' digital competencies.